Pelatihan Pemanfaatan Teknologi Informasi Untuk Membangun Personal Branding Strateginya Pada Siswa SMA Negeri 12 Kota Jambi - Agustini, Silvia Rianti; Hendri; Rozi, Syamsyida; Imelda Yose (Jurnal Pengabdian Masyarakat UNAMA, 2024)
of each person in the digital space or social media. The Training on Building Personal Branding in the Digital Space and its Strategy aims to provide understanding and insight to the students of SMAN 12 Jambi City about the importance of building self-branding or personal branding in the digital era. Apart from providing a positive perception to the public, it can also provide opportunities for female students of SMAN 12 Jambi City to get jobs that suit the interests and skills of students of SMAN 12 Jambi City through personal branding. Apart from training in building self-branding, participants will also be given knowledge about strategies for building self-branding in the digital space so that they will leave a positive digital footprint on social media.